2008
DOI: 10.1007/s11334-007-0043-y
|View full text |Cite
|
Sign up to set email alerts
|

Employing use cases to early estimate effort with simpler metrics

Abstract: In order to calculate size and to estimate effort in applications, the standard method most usually used is function points, which has been used with good results in the development of industrial software for some time. However, some aspects should be improved, namely: the time at which the estimation of effort is performed and the margin of error in the effort estimation. Consequently, another size metric which could be used to obtain more accurate estimations should be found. This article presents two other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 15 publications
0
45
0
Order By: Relevance
“…Authors in (Diev, 2006) and (Anda et al, 2001) worked on adjustment factors, while others in (Anda et al, 2001) and (Arnold and Pedross, 1998) highlighted the discrepancies in designing use case models. Researchers in (Robiolo and Orosco, 2008), (Robiolo et al, 2009) and (Ochodek and Nawrocki, 2008) proposed different size metrics such as transactions, TTPoints and paths, while others (Periyasamy and Ghode, 2009;Wang et al, 2009;Schneider and Winters, 2001;Braz and Vergilio, 2006;Nassif et al, 2011a,b;Mohagheghi et al, 2005;Ochodek et al, 2011) went further to extend the UCP model by providing new complexity weights or by modifying the method used to predict effort.…”
Section: Related Workmentioning
confidence: 99%
“…Authors in (Diev, 2006) and (Anda et al, 2001) worked on adjustment factors, while others in (Anda et al, 2001) and (Arnold and Pedross, 1998) highlighted the discrepancies in designing use case models. Researchers in (Robiolo and Orosco, 2008), (Robiolo et al, 2009) and (Ochodek and Nawrocki, 2008) proposed different size metrics such as transactions, TTPoints and paths, while others (Periyasamy and Ghode, 2009;Wang et al, 2009;Schneider and Winters, 2001;Braz and Vergilio, 2006;Nassif et al, 2011a,b;Mohagheghi et al, 2005;Ochodek et al, 2011) went further to extend the UCP model by providing new complexity weights or by modifying the method used to predict effort.…”
Section: Related Workmentioning
confidence: 99%
“…The research work concluded that "use case point" method is perhaps the best available tool for effort estimation of software development projects and highlighted that generalized standardization of "use case point" method will be an important contribution to software industry. Robiolo, G. and Orosco R. (2008) [18] had given more stress on the versatility of use case point method which can be employed to estimate the effort in early stages of development. The research work was intended to find out an alternative method for estimating software effort which can give better performance when compared to function-point method of software effort estimation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Unfortunately, only a few approaches used use cases to estimate the testing effort. Use cases have, however, been used in many studies to estimate the software development effort (cost) [e.g., 18,22,27,[29][30][31]. Nageshwaran [28] presents a use cases based approach for test effort estimation considering weight and environmental factors.…”
Section: Related Workmentioning
confidence: 99%